Virtual War and Magical Death : Technologies and Imaginaries for Terror and Killing - Finnström, Sverker; Whitehead, Neil L. (Book collections on Project MUSE., 2013)
The contributors to this provocative collection scrutinize the relations between anthropology and contemporary global war, contending that modern high-tech warfare is analogous to rituals of magic and sorcery, and examining the U.S. military's exploitation of ethnographic research.